2021
DOI: 10.1097/md.0000000000025702
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury in a pediatric patient with diabetic ketoacidosis

Abstract: Rationale: Diabetic ketoacidosis (DKA) can cause several complications. Among them, cardiac complications are the most fatal and difficult to detect. Cardiac markers are prognostic factors for morbidity and mortality in adult patients with DKA. But, there have been very few discussed cases in pediatrics. We report a case of severe DKA in child with elevated cardiac enzymes and prolonged QT interval. Patient concerns: A 12-year-old girl admitted by nause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Interestingly, a recently published study reported a significant increase in troponin and NT-proBNP levels and QTs prolongation in a 12-yr-old patient with moderate DKA (pH 7.11; HCO 3 7.1 mEq/L). This patient was slightly younger than ours, had uncontrolled T1D (5 yr duration), and most importantly, had a fever and high inflammatory markers during DKA, all of which may contribute to myocardial injury ( 7 ).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Interestingly, a recently published study reported a significant increase in troponin and NT-proBNP levels and QTs prolongation in a 12-yr-old patient with moderate DKA (pH 7.11; HCO 3 7.1 mEq/L). This patient was slightly younger than ours, had uncontrolled T1D (5 yr duration), and most importantly, had a fever and high inflammatory markers during DKA, all of which may contribute to myocardial injury ( 7 ).…”
Section: Discussionmentioning
confidence: 81%
“…This is a novel case of severe DKA associated with mild myocardial dysfunction and disproportionately elevated NT-proBNP and troponin levels in a newly diagnosed T1D in an adolescent. As mentioned earlier, to the best of our knowledge, only three cases of myocardial injury have been observed in pediatric patients with severe new-onset DKA ( 5 , 6 , 7 ). In all of the above cases, patients experienced a fulminant clinical course of the disease with severe complications, while troponin levels were mildly elevated.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“… 5 , 6 However, there are few case reports regarding myocardial damage in pediatric DKA patients. 7 , 8 In addition, some investigations have concluded that elevated troponin levels during DKA increase future mortality risk. 9 …”
mentioning
confidence: 99%
“…The available studies and case reports on myocardial involvement in the pediatric age group are rare. Shim et al 7 reported a 12-year-old girl with an elevated troponin level and myocardial injury during severe DKA. The changes were entirely resolved after 5 days of supportive care, and she was discharged without sequelae.…”
mentioning
confidence: 99%